National Lampoon's Animal house [videorecording (DVD)] - Landis, John, 1950-; Hulce, Tom, 1953-; Bacon, Kevin, 1958-; Belushi, John; Allen, Karen, 1951-; Sutherland, Donald, 1935- (Universal, 2003)
Faber College has one frat house so disreputable it will take anyone. The campus's only other frat house is full of white, anglo-saxon, rich young men that no one can stand except Dean Wormer. The dean enlists the help of their fraternity to get the boys of Delta House off campus. The dean's plan comes into play just before the homecoming parade.